Eksperimental karakteristik api dari suplai udara pada pembakaran uap partalite-partamax - A'yan Sabitah; Ichwan Noor Ardiyat (TURBO [Tulisan Riset Berbasis Online], 2022)
Partamax and partalate fuel are used as vehicle fuel in parts of the world, especially in Indonesia. Partamax and partalate have their own characteristics and if they are mixed, they will change the physicochemical properties of the pure fuel and affect the combustion behavior. In this study, an experiment was conducted on the combustion of partamax vapor, partalate and a mixture of partamax and partalate by varying the air supply by 1 liter/minute, 2 liters/minute and 3 liters/minute. The results of the combustion of fuel vapors were observed in the form of temperature by measuring using a thermocouple placed in two places with a height of 20 mm and 40 mm from the nozzle mouth and observing the flame using a camera. The results obtained from the observations are the flow of fire produced in the form of a laminar flame of all fuels, The highest flame temperature is owned by partamax fuel with an air supply of 3 liters/minute of 1047 oC on a thermocouple at an altitude of 20 mm and 1027 oC at an altitude of 40 mm, while the lowest temperature is owned by partalate fuel. This is because the octane value of partamax is higher. As the octane value increases, the flame temperature increases, but the flame height decreases. In addition, when the air supply is 3 liters/minute, a lift off phenomenon occurs in the partamax fuel and partamax-partalate mixture. This is because the octane value of partamax is higher. As the octane value increases, the flame temperature increases, but the flame height decreases. In addition, when the air supply is 3 liters/minute, a lift off phenomenon occurs in the partamax fuel and partamax-partalate mixture. This is because the octane value of partamax is higher. As the octane value increases, the flame temperature increases, but the flame height decreases. In addition, when the air supply is 3 liters/minute, a lift off phenomenon occurs in the partamax fuel and partamax-partalate mixture.